Evidence for publicly reported quality indicators in residential long-term care: a systematic review - Magdalena Osińska; Lauriane Favez; Franziska Zúñiga (BMC, 2022)
Abstract Background An increasing number of countries are using or planning to use quality indicators (QIs) in residential long-term care. Knowledge regarding the current state of evidence on usage and methodological soundness of publicly reported clinical indicators of quality in nursing homes is needed. The study aimed to answer the questions: 1) Which health-related QIs for residents in long-term care are currently publicly reported internationally? and 2) What is the methodological quality of these indicators? Methods A systematic search was conducted in the electronic databases PubMed, CINAHL and Embase in October 2019 and last updated on August 31st, 2022. Grey literature was also searched. We used the Appraisal of Indicators through Research and Evaluation (AIRE) instrument for the methodological quality assessment of the identified QIs. Results Of 23'344 identified records, 22 articles and one report describing 21 studies met the inclusion criteria. Additionally, we found 17 websites publishing information on QIs. We identified eight countries publicly reporting a total of 99 health-related QIs covering 31 themes. Each country used between six and 31 QIs. The most frequently reported indicators were pressure ulcers, falls, physical restraints, and weight loss. For most QI sets, we found basic information regarding e.g., purpose, definition of the indicators, risk-adjustment, and stakeholders' involvement in QIs' selection. Little up to date information was found regarding validity, reliability and discriminative power of the QIs. Only the Australian indicator set reached high methodological quality, defined as scores of 50% or higher in all four AIRE instrument domains. Conclusions Little information is available to the public and researchers for the evaluation of a large number of publicly reported QIs in the residential long-term care sector. Better reporting is needed on the methodological quality of QIs in this setting, whether they are meant for internal quality improvement or provider comparison.